2006
DOI: 10.1196/annals.1354.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid Restriction on Mitochondrial Free Radical Production and Oxidative DNA Damage

Abstract: Many studies have shown that caloric restriction (40%) decreases mitochondrial reactive oxygen species (ROS) generation in rodents. Moreover, we have recently found that 7 weeks of 40% protein restriction without strong caloric restriction also decreases ROS production in rat liver. This is interesting since it has been reported that protein restriction can also extend longevity in rodents. In the present study we have investigated the possible role of dietary lipids in the effects of caloric restriction on mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…However, the results of the present investigation rule out this possibility since it was found that 8.5% CR does not modify mitochondrial ROS generation. Thus, the present results, together with the previous ones concerning 40% CR (Gredilla et al 2001;Gredilla and Barja 2005), 40% protein restriction (Sanz et al 2004), 40% carbohydrate restriction (Sanz et al 2006a), and 40% lipid restriction (Sanz et al 2006b) demonstrate that the lower dietary intake of the proteins themselves is responsible for the decrease in mitochondrial ROS generation and oxidative damage to mtDNA that is observed during 40% CR.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, the results of the present investigation rule out this possibility since it was found that 8.5% CR does not modify mitochondrial ROS generation. Thus, the present results, together with the previous ones concerning 40% CR (Gredilla et al 2001;Gredilla and Barja 2005), 40% protein restriction (Sanz et al 2004), 40% carbohydrate restriction (Sanz et al 2006a), and 40% lipid restriction (Sanz et al 2006b) demonstrate that the lower dietary intake of the proteins themselves is responsible for the decrease in mitochondrial ROS generation and oxidative damage to mtDNA that is observed during 40% CR.…”
Section: Discussionsupporting
confidence: 77%
“…*(P < 0.05), **(P < 0.01), ***(P < 0.001) Biogerontology (2007) 8: 555-566 561 On the other hand, the lack of effect of 8.5% CR is important concerning the final identification of the dietary factor responsible for the well know decrease in mitochondrial ROS production in 40% CR. In previous studies we have found that both 40% CR (Gredilla et al 2001) and 40% protein restriction (Sanz et al 2004) decrease mitochondrial ROS production at complex I and oxidative damage to mtDNA in rat liver, whereas neither carbohydrate (Sanz et al 2006a) nor lipid restriction (Sanz et al 2006b) brought about these changes. This strongly suggested that restriction of the proteins themselves was responsible for this CR effect.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Particularly, protein restriction, PR, where a percentage of calories derived from protein is replaced by fat or carbohydrate, has been investigated in rodents and decreases in mitochondrial reactive oxygen species production and DNA and protein oxidative modifications have been reported , which could explain the increase in lifespan previously reported for PR (Leto et al, 1976). Similar effects were obtained with reduction of the amino acid methionine , but they could not be replicated by restricting lipid intake alone (Sanz et al, 2006a) or carbohydrate intake alone (Sanz et al, 2006b). IF, a regimen of either alternate day fasting or fasting for a day after 2 days of feeding, both increases lifespan and delays or prevents some age-related diseases (reviewed in Mattson & Wan, 2005).…”
Section: Caloric Restrictionsupporting
confidence: 60%